2020
DOI: 10.3389/fmars.2020.587454
|View full text |Cite
|
Sign up to set email alerts
|

The IAG-Switch and Further Transcriptomic Insights Into Sexual Differentiation of a Protandric Shrimp

Abstract: The insulin-like androgenic gland hormone (IAG) secreted from the androgenic gland (AG) is a unique endocrine controller (the IAG-switch) of crustacean sexual differentiation. However, while previous studies of the IAG-switch focused mainly on sexual differentiation at early developmental stages of gonochoristic species, this mechanism is yet to be deciphered during naturally occurring sexual shifts in hermaphrodite species. The Northern spot shrimp, Pandalus platyceros, is a protandric hermaphrodite species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 50 publications
(60 reference statements)
3
19
0
Order By: Relevance
“…Contrary to the controls, shrimp in the Lvit-IAG2 silencing treatments exhibited decreased volume of the ovarian region, and germ cells were much smaller and arranged in a disorganized mass. It is interesting to note that silencing IAG gene in another hermaphrodite shrimp P. platyceros induced feminization of individuals, including Vg expression in the hepatopancreas and ovarian development (Levy et al, 2020a), which is consistent with studies in dioecious species. Different outcome might be Ovarian regions of the shrimp from the Lvit-IAG2 silencing treatment were more transparent and smaller in relative size (C).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Contrary to the controls, shrimp in the Lvit-IAG2 silencing treatments exhibited decreased volume of the ovarian region, and germ cells were much smaller and arranged in a disorganized mass. It is interesting to note that silencing IAG gene in another hermaphrodite shrimp P. platyceros induced feminization of individuals, including Vg expression in the hepatopancreas and ovarian development (Levy et al, 2020a), which is consistent with studies in dioecious species. Different outcome might be Ovarian regions of the shrimp from the Lvit-IAG2 silencing treatment were more transparent and smaller in relative size (C).…”
Section: Discussionsupporting
confidence: 84%
“…In decapod species, IAG was first identified in the androgenic gland (AG) of the red-claw crayfish Cherax quadricarinatus in 2007 (Manor et al, 2007). Since then, numerous studies have found IAG in dioecious (Ventura et al, 2009;Rosen et al, 2010;Ventura et al, 2012;Chung, 2014;Huang et al, 2014), parthenogenetic (Levy et al, 2017), and hermaphroditic (Zhang et al, 2017;Levy et al, 2020a;Liu et al, 2020) species. Furthermore, its critical role in sexual differentiation has been properly studied via loss-of-function experiments (Ventura et al, 2012;Zmora and Chung, 2014;Priyadarshi et al, 2017;Fu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we collected samples of H. inermis at different stages of the species' protandric life cycle and constructed RNA libraries that yielded both known and novel, yet unannotated, sex-specific genes that are assumed to be associated with sexual differentiation and reproduction. To obtain insight into the function of these novel genes, we also performed a comparative in silico analysis with P. platyceros, taking advantage of RNA libraries of specific tissues previously obtained over the life cycle of P. platyceros (Levy et al, 2020a). P. platyceros is particularly suitable for such an analysis for two reasons: (i) taxonomically, the two species, H. inermis and P. platyceros, belong to families -Pandalidae and Hippolytidae, respectively (Martin et al, 2009) -that are closely related within the infraorder Caridea (Christoffersen, 1990;Wolfe et al, 2019;Levy et al, 2020c), and (ii) technically, the RNA for the H. inermis libraries was extracted from the entire body of the animal (due to its small size that prevented dissection of specific tissues), while the RNA for constructing P. platyceros libraries was obtained by dissecting out specific tissues (Levy et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain insight into the function of these novel genes, we also performed a comparative in silico analysis with P. platyceros, taking advantage of RNA libraries of specific tissues previously obtained over the life cycle of P. platyceros (Levy et al, 2020a). P. platyceros is particularly suitable for such an analysis for two reasons: (i) taxonomically, the two species, H. inermis and P. platyceros, belong to families -Pandalidae and Hippolytidae, respectively (Martin et al, 2009) -that are closely related within the infraorder Caridea (Christoffersen, 1990;Wolfe et al, 2019;Levy et al, 2020c), and (ii) technically, the RNA for the H. inermis libraries was extracted from the entire body of the animal (due to its small size that prevented dissection of specific tissues), while the RNA for constructing P. platyceros libraries was obtained by dissecting out specific tissues (Levy et al, 2020a). Therefore, our working hypothesis for the in silico analysis part of this study was that a search for homologs to the newly discovered H. inermis genes in transcriptomic libraries of P. platyceros (and other decapod crustaceans) might reveal the function of those genes in a more general context that includes a wider range of crustaceans.…”
Section: Introductionmentioning
confidence: 99%